Humanizing the robot: Kaliningrad’s House of Soviets and the state of decay - Michael Amundsen (Ambiances)
This article addresses the House of Soviets, the most prominent building in the centre of Kaliningrad, Russia. Using Juhani Pallasmaa’s theory of “sixth sense”, the building is seen through notions of atmospheres and diffusion, rather than the focused attention implied by its formalist construction. Local people have nicknamed the building the “monster” or “robot”, for its giant size and forbidding appearance. However, its status as an urban ruin implies spatial and temporal meanings that have “humanized” the building. The article focuses on the experience of urban exploration in the House of Soviets for one afternoon in the spring of 2013 with two Kaliningrad residents. This paper avers that the changing form of the House of Soviets in its state of decay promotes its appreciation as a work of art as it falls apart. Decrepitude and pillage, vandalism and littering are reclaiming the space as it promotes sensory imagination and engagement with “the terror of time”. The article includes photographs taken while exploring the building.